Climate Change Skepticism in the Face of Catastrophe - Mark Kagan (Tinbergen Institute, 2012)
This paper develops a general-equilibrium model of skill-biased technological change that approximates the observed shifts in the shares of wage and non-wageincome going to the top decile of U.S. households since 1980. Under realisticassumptions, we find that all agents can benefi…t from the technology change,provided that the observed rise in redistributive transfers over this period istaken into account. We show that the increase in capital's share of total incomeand the presence of capital-entrepreneurial skill complementarity are two keyfeatures that help support the wages of ordinary workers as the new technologydiffuses.
urn:NBN:nl:ui:31-1871/38768
Keywords: E32; E44; H23; O33; 330; Income Inequality; Skill-biased Technological Change; Capital-skill Complementarity; Redistribution; Welfare; Klimawandel; Katastrophe; Öffentliche Meinung; Zeitpräferenz; Wohlfahrtstheorie